Evaluating The Efficacy Of Muscle Stimulation In The Management Of Degenerative-Dystrophic Changes In The Cervical Spine - Melkonyan, Armenuhi
Degenerative-dystrophic changes in the cervical spine are a common cause of chronic pain and functional impairment, affecting millions of individuals globally. These conditions often result in reduced mobility, muscle atrophy, and declining quality of life. In recent years, muscle stimulation has emerged as a promising adjunctive therapy to improve muscle function and alleviate symptoms. This study evaluates the effectiveness of muscle stimulator application during treating patients with dystrophic-degenerative changes in the cervical spine. A cohort of 10 patients, aged 40-50, diagnosed with cervical degenerative conditions, participated in this randomized controlled trial. Participants were divided into two groups: one receiving conventional physical therapy alone and the other receiving combined therapy using a muscle stimulator targeting the cervical musculature. Over a 12-week intervention period, both groups were assessed using the Visual Analog Scale (VAS) for pain, the Neck Disability Index (NDI), and electromyography (EMG) to measure muscle activity. These findings suggest that muscle stimulator application is a valuable adjunct to conventional therapies, offering a non-invasive and effective means of managing dystrophic-degenerative changes in the cervical spine. Future research should explore the long-term benefits of this intervention and its potential to prevent the progression of cervical spine degeneration
Keywords: Cervical spine